Elevating job performance through job characteristics and work involvement - Johari, Johanim; Tan, Fee Yean; Yahya, Khulida Kirana; Adnan, Zurina (International Academic Research Journal, 2015)
The primary objective of this study is to assess the predicting role of job characteristics on job performance.Dimensions in the job characteristics construct are skill variety, task identity, task significance, autonomy, and feedback.Further, work involvement is tested as a mediator in the hypothesized link.A total of 151 public servants reported on their job characteristics and work involvement while supervisory-ratings were used to assess their level of job performance in terms of task performance and organizational citizenship behavior (OCB).SPSS version 14 and Smart PLS 2.0 were used for statistical analyses of the data.The findings revealed that feedback significantly and indirectly influence job performance and the relationships were mediated by work involvement.Overall, this study has managed to substantiate a marginal support for the Job Characteristics Theory.